Analyzing the U.S. Post-marketing safety surveillance of COVID-19 vaccines - Omar M. Albalawi; Maha I. Alomran; Ghada M. Alsagri; Turki A. Althunian; Thamir M. Alshammari (Elsevier, 2022)
Introduction: Since December 2020, three COVID-19 vaccines have been authorized in the United States (U.S.) and were proceeded by large immunization programs. The aim of this study was to characterize the U.S. post-marketing safety (PMS) profiles of these vaccines with an in-depth analysis of mortality data. Methods: This was a retrospective database analysis study. Details of the U.S. PMS reports (15 December 2020 to 19 March 2021) of the three vaccines (Pfizer-BioNTech, Moderna, and Janssen Ad26.COV2.S) were retrieved from the U.S. Vaccine Adverse Event Reporting System (VAERS). A descriptive analysis was conducted to characterize the reported adverse events (AEs). A comparative (Pfizer-BioNTech vs. Moderna) analysis of mortality was conducted. The mean count ratio of death between the two vaccines was estimated using a negative binomial regression model adjusting for the measured confounders. Results: A total of 44,451 AE reports were retrieved (corresponding to 0.05% of the U.S. population who received at least one dose). The most commonly reported AEs were injection site reactions (30.4% of the reports), pain (reported in 26.7% of the reports), and headache (18.6% of the reports). Serious AEs were reported in only 14.6% of the reports with 4,108 hospitalizations. The total number of deaths was 1,919 with a mean count ratio of Moderna (n = 997) vs. Pfizer-BioNTech (n = 899) of 1.07 (95% confidence interval 0.86 to 1.33). Conclusions: The vast majority of PMS AEs in the U.S. were non-serious, and the number of serious AEs is very low given the total number of vaccinated U.S. population.